A study of ovarian autotransplantation without vascular a pedicle in rats - Risvanli, Ali; Timurkan, Huseyin; Akpolat, Nusret; Gulacti, Irem; Ulakoglu, Erdal (Springer/Plenum Publishers, 2006)
Purpose: The study aimed to determine effects of FSH applications on follicle survival, development and hormone output and antigenicity of rat ovarian tissue autografts placed at subcutaneous or subperitoneal sites. Methods: A total of sixteen female rats were used in the study. The animals were divided into three groups. Ovaries were dissected and then transplanted under the peritoneum in the first group animals (n = 5) or under the skin in the second group animals (n = 6). And the animals in the third group (n = 5) were sham operated. Following operations, intramuscular injection of 8 IU of rhFSH were made daily to the animals in first and second groups from the first day of operation through thirty days. Vaginal irrigation samples were prepared daily from the animals for 30 days. The concentrations of serum estradiol and antiovarian antibodies in the blood were determined using ELISA on the last day of vaginal irrigations. Histopathological examination of the ovaries that were transplanted was made. Results: Results showed that cyclic variations were noticed in the samples of vaginal irrigation by day 30 in the animals of first and second groups. However, no significant differences were seen between groups. The concentration of blood serum estradiol was higher in the animals of first group. Decrease in numbers of primary follicles were found in the animals of second group and lesser corpus luteum were found in the animals of control group on the histopathological examinations of transplanted ovaries. All rats in the first and second groups were defined as seropositive for antiovarian antibodies. When the OD values were compared between first and second groups, it was identified that the OD values of rats in the first group was higher than it was seen in the second group. Conclusion: The ovarian transplantation without vascular pedicle in rats is characterized by follicular hyperplasia endocrinologically functional. Being seropositive of all rats in first and second groups in terms of antiovarian antibodies is an indicator to these antibodies does not affect the functions of transplanted ovaries. It is believed that the highness of OD values in the group which is transplanted beneath the peritoneum is based on the highness of estradiol concentrations in these animals.
Keywords: ovary; transplantation; FSH; antiovarian antibodies; rat